Bish bash bosh! - Firth, Henry; Theasby, Ian (HQ, 2019)
In Bish Bash Bosh! you'll discover a whole world of quick eats, weeknight suppers, showstopping feasts, and incredible sweet treats - all using the power of plants. From a hearty, classic lasagne to an indulgent mini banoffee meringue, and from quick quesadillas to an incredible curry house jalfrezi, these are simple, savvy recipes that you'll turn to time and again.